A porous electrode plate, a method for manufacturing the same, and a secondary battery
Patent Information
- Application Number
- CN202610049713.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-01-14
- Publication Date
- 2026-10-23
AI Technical Summary
机械冲压法是通过模具对电极进行压印,形成孔洞阵列,适合大规模生产,但是工艺参数要求苛刻,否则容易对电极产生不可逆破坏
本申请实施例提供的制备方法中,采用聚乙二醇-聚乳酸共聚物颗粒作为模板,聚乙二醇-聚乳酸共聚物分子结构中有较弱化学键(如酯键),受热时可优先断裂,并引发一系列协同降解反应,逐步分解成CO、CO2、甲醛、乙醛、水等小分子,这些小分子在热处理温度下可挥发去除,并在原位留下孔隙,且形成的孔隙大小和分布均匀,从而增加电解液对极片的浸润性,改善二次电池的快充性能。
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This application relates to the field of secondary battery technology, and in particular to a porous electrode, its preparation method and a secondary battery. Background Technology
[0002] With the development of new energy vehicles, the market demands increasingly higher driving range and charging speeds. Consequently, the industry is developing secondary batteries with higher energy density and charging rates to meet these market demands. In cell design, increasing the areal density and compaction density of the electrodes to increase the active material load per unit area and volume is an effective way to improve battery energy density. However, increasing the areal density and compaction density of the electrodes reduces the overall porosity of the electrodes, making electrolyte wetting difficult and affecting ion diffusion, thus deteriorating the cell's fast-charging capability.
[0003] To address the aforementioned issues, perforated electrode technology is commonly used. This involves creating 10-50 μm pores on or inside the electrode surface using physical or chemical methods. This effectively increases the electrode's porosity, expands the rapid penetration channels for the electrolyte, increases the contact area between the active material and the electrolyte, and enhances reaction kinetics. Simultaneously, the perforated structure provides a buffer space for the electrode.
[0004] Currently, electrode drilling methods include laser drilling, template method, and mechanical stamping. Laser drilling works by using a high-precision laser to ablate regular holes on the electrode surface. This method offers high controllability but is costly. The template method involves adding decomposable inert modules to the electrode. These modules are then decomposed through heat treatment to form pores. This method requires high-quality inert materials, limiting the types that can be used. Mechanical stamping uses a die to imprint an array of holes on the electrode, making it suitable for mass production. However, it requires stringent process parameters; otherwise, irreversible damage to the electrode can occur.
[0005] For the template method, KR1020200123456A uses polycarbonate microspheres as a template and adds the organometallic catalyst zinc acetylacetonate, reducing the decomposition temperature from 220℃ to 180℃. However, the zinc ions remaining after catalyst decomposition may react with components such as LiPF6 in the electrolyte to generate ZnF2, consuming active lithium. One approach uses SiO2-coated organic naphthalene as a template, removing it after rolling under low-temperature vacuum treatment at 80-100℃. However, naphthalene is toxic to humans and is classified as a Group 2B carcinogen, posing a high risk. US20210028214A1 uses a mixed salt of ammonium oxalate and ammonium bicarbonate as a template, decomposing at high temperatures to produce NH3 and CO2. However, NH3 easily combines with water vapor and reacts with the copper foil of the current collector, corroding and damaging it.
[0006] To address the problems existing in the above-mentioned technologies, it is necessary to develop a novel template-based electrode drilling method. Summary of the Invention
[0007] This application aims to at least solve one of the technical problems existing in the prior art. To this end, this application provides a porous electrode, its preparation method, and a secondary battery. This application uses polyethylene glycol-polylactic acid copolymer particles as a template to prepare the porous electrode, without using volatile toxic substances. The template decomposition products do not corrode the electrode, and there are no residual metal ions or other substances that easily react with the electrolyte and degrade battery performance. Furthermore, the prepared porous electrode has uniform pore size and distribution, which is beneficial for improving the fast-charging performance of the secondary battery.
[0008] To achieve this objective, the following technical solution is adopted in this application: In a first aspect, this application provides a method for preparing a porous electrode sheet, the method comprising the following steps: Electrode active material, conductive agent, binder, polyethylene glycol-polylactic acid copolymer particles and solvent are mixed to prepare electrode slurry, wherein the polyethylene glycol-polylactic acid copolymer particles are insoluble in the solvent; The electrode paste is coated on at least one side of the current collector, and after drying and rolling, the electrode paste on the surface of the current collector forms an electrode active layer precursor, thus obtaining an electrode precursor. The electrode precursor is heat-treated to decompose the polyethylene glycol-polylactic acid copolymer and generate pores, thus obtaining a porous electrode.
[0009] In some embodiments of this application, the Dv of the polyethylene glycol-polylactic acid copolymer particles 50 With the Dv of the electrode active material 50 The ratio is 0.1-2:1.
[0010] In some embodiments of this application, the thermal decomposition temperature of the polyethylene glycol-polylactic acid copolymer is 150-200°C.
[0011] In some embodiments of this application, the weight-average molecular weight of the polyethylene glycol-polylactic acid copolymer is 3000-10000 Da.
[0012] In some embodiments of this application, the polyethylene glycol-polylactic acid copolymer contains 80-85 wt% polyethylene glycol and 15-20 wt% polylactic acid.
[0013] In some embodiments of this application, the mass content of the polyethylene glycol-polylactic acid copolymer particles in the electrode active layer precursor is 0.1-1%.
[0014] In some embodiments of this application, the electrode active layer precursor comprises, by weight percentage: 1-10% conductive agent, 2-10% binder, 0.1-1% polyethylene glycol-polylactic acid copolymer particles, and the balance being electrode active material.
[0015] In some embodiments of this application, the electrode active layer precursor further includes 0.5-1 wt% thickener.
[0016] In some embodiments of this application, the heat treatment temperature is T~T+25℃, where T is the thermal decomposition temperature of the polyethylene glycol-polylactic acid copolymer.
[0017] In some embodiments of this application, the heat treatment time is 10-120 min.
[0018] In some embodiments of this application, the heat treatment is performed under vacuum conditions of -40 to -80 kPa.
[0019] In some embodiments of this application, the step of preparing the electrode precursor includes: The components of the electrode active layer precursor and the solvent are mixed to prepare an electrode slurry; The electrode slurry is coated on at least one side of the current collector, and after drying and rolling, the electrode precursor is obtained.
[0020] In some embodiments of this application, the solid content of the electrode slurry is 30-60%.
[0021] In some embodiments of this application, the porous electrode sheet is a negative electrode sheet, and the compaction density of the electrode active layer precursor in the electrode sheet precursor is 1.4-1.8 g / cm³. 3 .
[0022] In some embodiments of this application, the porous electrode sheet is a positive electrode sheet, and the compaction density of the electrode active layer precursor in the electrode sheet precursor is 2.1-3.8 g / cm³. 3 .
[0023] Secondly, this application provides a porous electrode sheet prepared by the preparation method described in the first aspect.
[0024] Thirdly, this application provides a secondary battery, which includes the porous electrode sheet described in the second aspect.
[0025] Compared with the prior art, this application has the following beneficial effects: In the preparation method provided in this application, polyethylene glycol-polylactic acid copolymer particles are used as templates. The polyethylene glycol-polylactic acid copolymer has weak chemical bonds (such as ester bonds) in its molecular structure, which can be preferentially broken when heated, and trigger a series of synergistic degradation reactions, gradually decomposing into small molecules such as CO, CO2, formaldehyde, acetaldehyde, and water. These small molecules can be volatilized and removed at the heat treatment temperature, leaving pores in situ. The pores formed are uniform in size and distribution, thereby increasing the wettability of the electrolyte to the electrode and improving the fast charging performance of the secondary battery.
[0026] Furthermore, the preparation method provided in this application does not use volatile toxic substances, ensuring high production safety; the decomposition products of polyethylene glycol-polylactic acid copolymer do not corrode the electrode; and after the decomposition of polyethylene glycol-polylactic acid copolymer, no metal ions or other substances that easily react with the electrolyte and deteriorate battery performance remain. Detailed Implementation
[0027] To better understand the above-mentioned objectives, features, and advantages of this application, the solution of this application will be further described below. It should be noted that, unless otherwise specified, the embodiments and features described in these embodiments can be combined with each other.
[0028] Many specific details are set forth in the following description in order to provide a full understanding of this application, but this application may also be implemented in other ways different from those described herein; obviously, the embodiments in the specification are only some embodiments of this application, and not all embodiments.
[0029] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs; the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit this application.
[0030] In this document, the term "embodiment" means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment or implementation of this application. The appearance of this phrase in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment mutually exclusive with other embodiments. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments. The term "implementation" as used herein has a similar understanding.
[0031] In the description of the embodiments of this application, the open-ended technical features or solutions described by words such as "containing," "comprising," and "including" do not exclude additional members beyond those listed unless otherwise specified. They can be considered as providing both closed-ended features or solutions composed of the listed members and open-ended features or solutions that include additional members beyond the listed members. For example, A includes a1, a2, and a3. Unless otherwise specified, it may also include other members or exclude additional members. This can be considered as providing both the feature or solution that "A consists of a1, a2, and a3" and the feature or solution that "A includes not only a1, a2, and a3, but also other members." In this application, unless otherwise specified, A (e.g., B) indicates that B is a non-limiting example of A, and it can be understood that A is not limited to B.
[0032] In the description of the embodiments in this application, the term "and / or" is merely a description of the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, and B existing alone. Additionally, the character " / " in this document generally indicates that the preceding and following related objects have an "or" relationship.
[0033] In the description of the embodiments of this application, the terms "multiple" or "multiple types" refer to a quantity greater than 2 or equal to 2. For example, "one or more" means one or more types.
[0034] The "range" described in the embodiments of this application can be defined in the form of a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints. Any endpoint can be independently included or excluded, and they can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60~120 and 80~110 are listed for a specific parameter, it is expected that ranges of 60~110 and 80~120 are also included. Furthermore, if minimum range values of 1 and 2 are listed, and maximum range values of 3, 4, and 5 are also listed, then the following ranges are all expected: 1~3, 1~4, 1~5, 2~3, 2~4, and 2~5. In this application, unless otherwise stated, the numerical range "a~b" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0~5" indicates that all real numbers between "0" and "5" have been listed in this article; "0~5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is described as an integer ≥ 2, it is equivalent to listing integers such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc. For instance, when a parameter is described as an integer selected from "2-10", it is equivalent to listing the integers 2, 3, 4, 5, 6, 7, 8, 9, and 10.
[0035] Those skilled in the art will understand that the order in which the steps are written in the methods of various embodiments or examples does not imply a strict execution order and does not constitute any limitation on the implementation process. The detailed execution order of each step should be determined by its function and possible internal logic. Unless otherwise specified, all steps of this application may be performed sequentially or randomly, preferably sequentially. For example, if the method includes steps (a) and (b), it means that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, if the method may also include step (c), it means that step (c) can be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.
[0036] In a first aspect, embodiments of this application provide a method for preparing a porous electrode sheet, the method comprising the following steps: Electrode active material, conductive agent, binder, polyethylene glycol-polylactic acid copolymer particles and solvent are mixed to prepare electrode slurry, wherein the polyethylene glycol-polylactic acid copolymer particles are insoluble in the solvent; The electrode paste is coated on at least one side of the current collector, and after drying and rolling, the electrode paste on the surface of the current collector forms an electrode active layer precursor, thus obtaining an electrode precursor. The electrode precursor is heat-treated to decompose the polyethylene glycol-polylactic acid copolymer and generate pores, thus obtaining a porous electrode.
[0037] It should be noted that the porous electrode in this embodiment includes a current collector and an electrode active layer located on at least one side of the current collector. The electrode active layer precursor refers to the precursor used to form the electrode active layer, which itself is a film structure.
[0038] In this embodiment, the polyethylene glycol-polylactic acid copolymer in the electrode precursor exists in particulate form to function as a pore-forming agent. Therefore, the solvent used to prepare the electrode slurry must ensure that the polyethylene glycol-polylactic acid copolymer particles remain granular and do not dissolve. Apart from this, this application does not impose other limitations on the solvent, and those skilled in the art can select from solvents known in the art for preparing electrode slurries. For example, for aqueous electrode active materials (such as aqueous lithium iron phosphate cathode materials for lithium batteries, polyanion cathode materials for sodium batteries, etc.), water can be used as the solvent; for non-aqueous electrode active materials, N-methylpyrrolidone (NMP) can be used as the solvent.
[0039] In the preparation method provided in this application, polyethylene glycol-polylactic acid copolymer particles are used as templates. The polyethylene glycol-polylactic acid copolymer has weak chemical bonds (such as ester bonds) in its molecular structure, which can be preferentially broken when heated, and trigger a series of synergistic degradation reactions, gradually decomposing into small molecules such as CO, CO2, formaldehyde, acetaldehyde, and water. These small molecules can be volatilized and removed at the heat treatment temperature, leaving pores in situ. The pores formed are uniform in size and distribution, thereby increasing the wettability of the electrolyte to the electrode and improving the fast charging performance of the secondary battery.
[0040] Furthermore, the preparation method provided in this application does not use volatile toxic substances, ensuring high production safety; the decomposition products of polyethylene glycol-polylactic acid copolymer do not corrode the electrode; and after the decomposition of polyethylene glycol-polylactic acid copolymer, no metal ions or other substances that easily react with the electrolyte and deteriorate battery performance remain.
[0041] In this embodiment, the porous electrode sheet can be either a positive or negative electrode sheet; the electrode active material can be either a positive or negative electrode active material. When the porous electrode sheet is a positive electrode sheet, the electrode active material is a positive electrode active material; when the porous electrode sheet is a negative electrode sheet, the electrode active material is a negative electrode active material.
[0042] In this embodiment, the selection of the electrode active material is related to the type of secondary battery. This application does not impose any special restrictions on the type of electrode active material; it can be any electrode active material known in the art for use in secondary batteries.
[0043] The following are some examples of electrode active materials. It will be readily understood by those skilled in the art that these electrode active materials are merely examples and should not be construed as limiting the scope of this application.
[0044] For lithium-ion secondary batteries, the positive electrode active material may include at least one of olivine-structured lithium-containing phosphates and lithium transition metal oxides. The olivine-structured lithium-containing phosphates include, but are not limited to, lithium iron phosphate (e.g., LiFePO4, LFP), carbon-coated lithium iron phosphate, lithium manganese phosphate (e.g., LiMnPO4), carbon-coated lithium manganese phosphate, lithium iron manganese phosphate, and carbon-coated lithium iron manganese phosphate. The lithium transition metal oxides include, but are not limited to, lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, and lithium nickel cobalt manganese oxide (NCM).
[0045] For sodium secondary batteries, the positive electrode active material may include at least one of sodium transition metal oxides, polyanionic compounds, and Prussian blue compounds.
[0046] The negative electrode active material may include one or more of graphite, soft carbon, hard carbon, elemental silicon, silicon oxide, and silicon-carbon composites.
[0047] In this embodiment, the type of conductive agent is not specifically limited, and it can be any conductive agent known in the art for use in secondary batteries. For example, the conductive agent may include one or more of superconducting carbon, acetylene black, conductive carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0048] In this embodiment, the type of binder is not specifically limited, and it can be any binder known in the art for use in secondary batteries. For example, for the positive electrode, the binder may include one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), ethylene-tetrafluoroethylene-propylene terpolymer, ethylene-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorinated acrylate resin. For the negative electrode, the binder may include one or more of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), and polymethacrylic acid (PMAA).
[0049] In this embodiment, the type of current collector is not specifically limited, and it can be any current collector known in the art for use in secondary batteries. For example, for the positive electrode, the current collector can be aluminum foil; for the negative electrode, the current collector can be copper foil.
[0050] In some embodiments of this application, the Dv of the polyethylene glycol-polylactic acid copolymer particles 50 With the Dv of the electrode active material 50 The ratio is 0.1-2:1; for example, it can be 0.1:1, 0.2:1, 0.3:1, 0.5:1, 0.6:1, 0.8:1, 1:1, 1.2:1, 1.3:1, 1.5:1, 1.6:1, 1.8:1, or 2:1, etc. However, this application is not limited to the listed values, and other unlisted values within this range are also applicable.
[0051] In this embodiment of the application, the Dv 50 Dv is the volume average particle size, which represents the particle size at which the cumulative volume percentage of the material particles reaches 50%. 50 The test can be performed using instruments and methods known in the art, such as laser particle size analyzers.
[0052] In this embodiment, controlling the particle size ratio of polyethylene glycol-polylactic acid (PEG-PLA) copolymer particles to electrode active material particles within the aforementioned range is beneficial for further improving the fast-charging performance of the battery. If the particle size ratio of PEG-PLA copolymer particles to electrode active material particles is too small, the PEG-PLA copolymer particles are more likely to disperse in the gaps between the electrode active material particles, occupying the existing gaps. In this case, the decomposition of PEG-PLA copolymer particles has a smaller effect on improving the porosity of the electrode sheet, and the electrode active material particles may still be in a relatively tight fit, which is not conducive to the entry of electrolyte and reduces the improvement effect on the fast-charging performance of the battery. If the particle size ratio of PEG-PLA copolymer particles to electrode active material particles is too large, the pores generated by the decomposition of PEG-PLA copolymer particles will be too large. Although this is beneficial for electrolyte wetting, it will also cause significant damage to the contact between the electrode active material particles, resulting in obstructed ion transport and a decrease in the improvement effect on the fast-charging performance of the battery.
[0053] In some embodiments of this application, the thermal decomposition temperature of the polyethylene glycol-polylactic acid copolymer is 150-200°C; for example, it can be 150°C, 155°C, 160°C, 165°C, 170°C, 175°C, 180°C, 185°C, 190°C, 195°C, or 200°C. However, this application is not limited to the listed values, and other unlisted values within this range are also applicable.
[0054] Currently, in the preparation process of positive and negative electrode sheets for secondary batteries, the positive and negative electrode slurries need to be coated onto the surface of the current collector, followed by drying and rolling. The coating and drying temperatures are generally 100-120℃. In the embodiments of this application, the thermal decomposition temperature of polyethylene glycol-polylactic acid copolymer is 150-200℃, which is beneficial for maintaining its stability during coating and drying. If the thermal decomposition temperature of polyethylene glycol-polylactic acid copolymer is too low, it may decompose to a certain extent during coating and drying, and the resulting pores will be destroyed by rolling. After heat treatment, the porosity of the porous electrode sheet will decrease, reducing the effect on improving the fast charging performance of the battery. If the thermal decomposition temperature of polyethylene glycol-polylactic acid copolymer is too high, its thermal decomposition will be more difficult, resulting in higher energy consumption (temperature) and longer processing time during subsequent heat treatment, and potentially higher residual amounts. Moreover, high-temperature heat treatment may also cause the decomposition of other components. For example, if there are defects in the thickener, it may cause the thickener to decompose thermally.
[0055] In some embodiments of this application, the weight-average molecular weight of the polyethylene glycol-polylactic acid copolymer is 3000-10000 Da; for example, it can be 3000 Da, 3500 Da, 4000 Da, 4500 Da, 5000 Da, 5500 Da, 6000 Da, 6500 Da, 7000 Da, 7500 Da, 8000 Da, 8500 Da, 9000 Da, 9500 Da, or 10000 Da. However, this application is not limited to the listed values, and other unlisted values within this range are also applicable.
[0056] In this embodiment, the weight-average molecular weight of the polyethylene glycol-polylactic acid copolymer is controlled within the range of 3000-10000 Da, which is beneficial for it to have a suitable thermal decomposition temperature and good dispersibility. If the molecular weight of the polyethylene glycol-polylactic acid copolymer is too small, its thermal decomposition temperature is low, and it may decompose to a certain extent during coating and drying. The resulting pores will be destroyed by rolling, and the porosity of the porous electrode sheet will decrease after heat treatment, thus reducing the effect on improving the fast charging performance of the battery. If the molecular weight of the polyethylene glycol-polylactic acid copolymer is too large, on the one hand, its thermal decomposition temperature is high, making thermal decomposition more difficult, resulting in higher energy consumption and longer processing time during subsequent heat treatment, and potentially higher residual content; on the other hand, the polyethylene glycol-polylactic acid copolymer particles are prone to agglomeration, resulting in poor particle dispersion uniformity. This leads to poor pore size and distribution uniformity in the resulting porous electrode sheet, further reducing the effect on improving the fast charging performance of the battery.
[0057] In some embodiments of this application, the polyethylene glycol-polylactic acid copolymer contains 80-85 wt% polyethylene glycol (e.g., 80 wt%, 80.5 wt%, 81 wt%, 81.5 wt%, 82 wt%, 82.5 wt%, 83 wt%, 83.5 wt%, 84 wt%, 84.5 wt%, or 85 wt%) and 15-20 wt% polylactic acid (e.g., 15 wt%, 15.5 wt%, 16 wt%, 16.5 wt%, 17 wt%, 17.5 wt%, 18 wt%, 18.5 wt%, 19 wt%, 19.5 wt%, or 20 wt%). However, this application is not limited to the listed values; other unlisted values within this range are also applicable.
[0058] In this embodiment, the content of polyethylene glycol (PEG) and polylactic acid (PLA) in the PEG-PLA copolymer is controlled within the aforementioned range, which is beneficial for further improving the fast-charging performance of the battery. If the PEG content is too high and the PLA content is too low, the thermal decomposition temperature of the PEG-PLA copolymer will be low, and a certain degree of decomposition may occur during coating and drying. The resulting pores will be damaged by rolling, and the porosity of the porous electrode sheet will decrease after heat treatment, reducing the effect on improving the fast-charging performance of the battery. In addition, it will also make the PEG-PLA copolymer more hydrophilic. For aqueous electrode active materials, the electrode slurry (with water as the solvent) is prone to moisture absorption, resulting in decreased processability and stability, and poor material distribution uniformity in the obtained porous electrode sheet. If the PEG content is too low and the PLA content is too high, the thermal decomposition temperature of the PEG-PLA copolymer will be high, making thermal decomposition more difficult, resulting in higher energy consumption during subsequent heat treatment, longer processing time, and potentially higher residual content.
[0059] In some embodiments of this application, the weight-average molecular weight of the polyethylene glycol-polylactic acid copolymer is 3000-10000 Da; and the polyethylene glycol content in the polyethylene glycol-polylactic acid copolymer is 80-85 wt%, and the polylactic acid content is 15-20 wt%. This combines the advantages of both, further improving the fast-charging performance of the battery.
[0060] In some embodiments of this application, the mass content of the polyethylene glycol-polylactic acid copolymer particles in the electrode active layer precursor is 0.1-1%; for example, it can be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, or 1%. However, this application is not limited to the listed values, and other unlisted values within this range are also applicable.
[0061] In this embodiment, the mass content of polyethylene glycol-polylactic acid copolymer particles in the electrode active layer precursor is controlled within the aforementioned range, which is beneficial for further improving the fast-charging performance of the battery. If the content of polyethylene glycol-polylactic acid copolymer particles is too low, the porosity of the resulting porous electrode will be low, resulting in a weaker effect on improving electrolyte wetting and battery fast-charging performance. If the content of polyethylene glycol-polylactic acid copolymer particles is too high, the porosity of the resulting porous electrode will be high. Excessive pores can easily cause significant damage to the contact between the electrode active material particles, leading to obstructed ion transport and a decrease in the improvement effect of battery fast-charging performance; moreover, the energy consumption for decomposing polyethylene glycol-polylactic acid copolymer particles will also increase.
[0062] In some embodiments of this application, the electrode active layer precursor comprises, by weight percentage: 1-10% conductive agent, 2-10% binder, 0.1-1% polyethylene glycol-polylactic acid copolymer particles, and the balance being electrode active material.
[0063] The conductive agent can have any mass content within the range of 1-10%, for example, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, or 10%. The adhesive can have any mass content within the range of 2-10%, for example, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, or 10%. The polyethylene glycol-polylactic acid copolymer particles can have any mass content within the range of 0.1-1%, for example, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, or 1%.
[0064] In this embodiment, the content of conductive agent and binder is controlled within the aforementioned suitable range. If their content is too low, the corresponding conductivity and bonding effect will be weakened; if their content is too high, the content of electrode active material will be reduced accordingly, which will cause the battery capacity and energy density to decrease.
[0065] In some embodiments of this application, the electrode active layer precursor further comprises a thickener of 0.5-1 wt%; for example, it may be 0.5 wt%, 0.55 wt%, 0.6 wt%, 0.65 wt%, 0.7 wt%, 0.75 wt%, 0.8 wt%, 0.85 wt%, 0.9 wt%, 0.95 wt%, or 1 wt%. However, this application is not limited to the listed values, and other unlisted values within this range are also applicable.
[0066] In this embodiment, no special limitation is placed on the type of thickener, which can be any thickener known in the art for use in secondary batteries. For example, the thickener can be carboxymethyl cellulose (CMC).
[0067] In this embodiment, the thickener helps improve the dispersion uniformity of the electrode slurry and the distribution uniformity of materials in the electrode sheet. If its content is too low, its effect will be weak; if its content is too high, the content of electrode active material will be reduced accordingly, which will decrease the battery capacity and energy density.
[0068] In some embodiments of this application, the composition of the electrode active layer precursor, by mass percentage, includes: 78-96.4% electrode active material, 1-10% conductive agent, 0.5-1% thickener, 2-10% binder, and 0.1-1% polyethylene glycol-polylactic acid copolymer particles.
[0069] In some embodiments of this application, the heat treatment temperature is T to T+25℃, for example, it can be T, T+5℃, T+10℃, T+15℃, T+20℃, T+25℃, etc. T is the thermal decomposition temperature of the polyethylene glycol-polylactic acid copolymer.
[0070] In this embodiment of the application, if the heat treatment temperature is too low, the thermal decomposition degree of the polyethylene glycol-polylactic acid copolymer particles will decrease, or even fail to decompose, the porosity of the porous electrode will decrease, and the amount of impurity residue will increase; if the heat treatment temperature is too high, the energy consumption will be high, and it may cause other components (such as binders) to decompose.
[0071] In some embodiments of this application, the heat treatment time is 10-120 min, for example, it can be 10 min, 20 min, 30 min, 40 min, 50 min, 60 min, 70 min, 80 min, 90 min, 100 min, 110 min or 120 min.
[0072] In this embodiment of the application, if the heat treatment time is too short, the degree of thermal decomposition of the polyethylene glycol-polylactic acid copolymer particles will decrease, the porosity of the porous electrode will decrease, and the amount of residual impurities will increase; if the heat treatment time is too long, the energy consumption will increase.
[0073] In some embodiments of this application, the heat treatment is performed under vacuum conditions.
[0074] In this embodiment, during heat treatment under vacuum conditions, polyethylene glycol-polylactic acid copolymer particles are more easily decomposed into small molecules such as CO, CO2, formaldehyde, acetaldehyde, and water. These small molecules are easily volatilized and removed at the heat treatment temperature. However, during heat treatment under aerobic conditions, the polyethylene glycol-polylactic acid copolymer particles are more prone to decomposition, producing higher molecular weight aldehydes or ketones as byproducts that are difficult to volatilize. This results in an increase in the amount of residual impurities in the resulting porous electrode, affecting battery performance. Furthermore, heat treatment under aerobic conditions also oxidizes the metal current collector, leading to a decrease in the electronic conductivity of the current collector.
[0075] In some embodiments of this application, the vacuum degree of the vacuum condition is -40 to -80 kPa; for example, it can be -80 kPa, -75 kPa, -70 kPa, -65 kPa, -60 kPa, -55 kPa, -50 kPa, -45 kPa, or -40 kPa, etc. However, this application is not limited to the listed values, and other unlisted values within this range are also applicable.
[0076] It should be noted that the vacuum value described in the embodiments of this application is the difference between the current air pressure and the standard atmospheric pressure.
[0077] In this embodiment, if the vacuum is too high (i.e., the absolute pressure is too low), it will lead to increased energy consumption, higher requirements for the airtightness of the equipment, and increased production costs. If the vacuum is too low (i.e., the absolute pressure is too high), there will be more residual oxygen in the environment, which will make the polyethylene glycol-polylactic acid copolymer more likely to decompose and generate non-volatile substances, increase the amount of non-volatile impurities in the porous electrode, and increase the oxide layer on the metal current collector.
[0078] In some embodiments of this application, the solid content of the electrode slurry is 30-60%; for example, it can be 30%, 32%, 35%, 38%, 40%, 42%, 45%, 48%, 50%, 52%, 55%, 58%, or 60%, etc. However, this application is not limited to the listed values, and other unlisted values within this range are also applicable.
[0079] In this embodiment, if the solid content of the electrode slurry is too low, the energy consumption during drying will be high and the production efficiency will be low; if the solid content of the electrode slurry is too high, the viscosity of the slurry will be high, the material will be easily dispersed unevenly, and the processing will be difficult.
[0080] In some embodiments of this application, the porous electrode sheet is a negative electrode sheet, and the compaction density of the electrode active layer precursor in the electrode sheet precursor is 1.4-1.8 g / cm³. 3 For example, it could be 1.4 g / cm³. 3 1.5 g / cm 3 1.6 g / cm3 1.7g / cm 3 Or 1.8 g / cm 3 wait.
[0081] In some embodiments of this application, the porous electrode sheet is a positive electrode sheet, and the compaction density of the electrode active layer precursor in the electrode sheet precursor is 2.1-3.8 g / cm³. 3 For example, it could be 2.1 g / cm³. 3 2.3 g / cm 3 2.5 g / cm 3 2.6g / cm 3 2.8 g / cm 3 3 g / cm 3 3.2 g / cm 3 3.3 g / cm 3 3.5 g / cm 3 3.6 g / cm 3 Or 3.8 g / cm 3 wait.
[0082] Specifically, for the positive electrode, the compaction density of the electrode active layer precursor can vary depending on the positive electrode active material. For example, when the positive electrode active material is lithium iron phosphate (LFP), the compaction density of the electrode active layer precursor can be 2.1-2.8 g / cm³. 3 The positive electrode active material is lithium nickel cobalt manganese oxide (NCM), and the compaction density of the electrode active layer precursor can be 3.1-3.8 g / cm³. 3 .
[0083] At the aforementioned compaction density, the resulting porous electrode sheet can exhibit a high specific capacity, which is beneficial for improving the energy density of the battery. However, this application is not limited to this, and those skilled in the art can select other compaction densities according to actual needs.
[0084] Secondly, this application provides a porous electrode sheet prepared by the preparation method described in the first aspect. Therefore, this porous electrode sheet possesses all the advantages of the aforementioned preparation method, which will not be elaborated further here.
[0085] Thirdly, this application provides a secondary battery comprising the porous electrode sheet described in the second aspect. Thus, this secondary battery possesses all the advantages of the aforementioned porous electrode sheet, which will not be elaborated further here.
[0086] In some embodiments of this application, the secondary battery includes a positive electrode, a separator, a negative electrode, and an electrolyte, wherein the separator is disposed between the positive electrode and the negative electrode; at least one of the positive electrode and the negative electrode is the porous electrode described in the second aspect.
[0087] In this embodiment of the application, the secondary battery can be a lithium-ion battery, a lithium metal battery, a sodium-ion battery, a sodium metal battery, a magnesium-ion battery, a magnesium metal battery, etc.
[0088] Those skilled in the art will readily understand that different active materials will be used for different secondary batteries and different electrodes (positive or negative). Therefore, the porous electrode sheet used must be matched to the application direction.
[0089] The active metal battery employs a structure design without a negative electrode or with a metal negative electrode, lacking a traditional negative electrode active layer. Therefore, the only positive electrode in the metal battery is the porous positive electrode provided in the first aspect of this application. The positive electrode of the active ion battery can be the porous positive electrode provided in the first aspect of this application, and the negative electrode can also be the porous negative electrode provided in the first aspect of this application.
[0090] To make the technical problems, technical solutions, and beneficial effects solved by this application clearer, the following will provide a more detailed description of this application in conjunction with embodiments. Obviously, the described embodiments are merely some embodiments of this application, and not all embodiments. The following description of at least one exemplary embodiment is merely illustrative and is in no way intended to limit this application or its applications. Based on the embodiments in this application, all other embodiments obtained by those skilled in the art without inventive effort are within the scope of protection of this application.
[0091] Where specific techniques or conditions are not specified in the examples, they shall be performed in accordance with conventional techniques or conditions in the art, techniques or conditions described in the literature, or product instructions. Reagents or instruments whose manufacturers are not specified are all commercially available conventional products.
[0092] Example 1 This embodiment provides a lithium-ion battery, the preparation method of which is as follows: (1) Preparation of positive electrode sheet LiNi, the positive electrode active material 0.8 Co 0.1 Mn 0.1 O2 (NCM811), conductive agent superconducting carbon black (SP), and binder PVDF are mixed in a mass ratio of 98:1:1, and solvent is added. N 1,3-methylpyrrolidone (NMP) was stirred until homogeneous to obtain a positive electrode slurry (solid content 50%). The positive electrode slurry was coated on both sides of the positive electrode current collector aluminum foil, air-dried at room temperature, and then transferred to a 115℃ vacuum drying oven for complete drying. Afterwards, it was rolled and punched to obtain the positive electrode sheet with a single-sided areal density of 20 mg / cm³. 2 The compacted density is 3.4 g / cm³. 3.
[0093] (2) Preparation of porous negative electrode sheet The negative electrode active material graphite, the conductive agent superconducting carbon black (SP), the thickener (CMC), the binder styrene-butadiene rubber (SBR), and polyethylene glycol-polylactic acid copolymer (PEG-PLA) particles were mixed in a mass ratio of 94.5:1.5:1:2:1, and then added to deionized water and stirred evenly to obtain a negative electrode slurry (solid content of 50%). The Dv of the graphite particles... 50 The Dv of PEG-PLA particles is 13μm. 50 It has a molecular weight of 15 μm, a weight-average molecular weight of 4500, a PEG content of 82.5%, and a PLA content of 17.5%. The negative electrode slurry was coated on both sides of the negative electrode current collector copper foil, air-dried at room temperature, and then transferred to a vacuum drying oven at 115℃ for complete drying. It was then rolled to obtain the negative electrode precursor, with a single-sided areal density of 20 mg / cm³. 2 The compacted density is 1.55 g / cm³. 3 ; The negative electrode precursor is placed in a vacuum heating winding machine for heat treatment. The vacuum degree is controlled at -60 kPa, the heating rate is 5℃ / min, the heating temperature is 180℃, and the heat treatment is carried out for 15 min to obtain a porous negative electrode.
[0094] (3) Electrolyte The electrolyte is a solution containing 1 mol / L LiPF6, wherein the solvent is composed of EC, EMC and DEC in a mass ratio of 30:50:20.
[0095] (4) Separator: PE is used as the separator.
[0096] (5) Battery assembly The positive electrode, separator, and porous negative electrode are stacked in sequence to obtain a bare cell. The tabs are welded to the bare cell, and the bare cell is placed in an aluminum-plastic film and baked at 80°C to remove water. The electrolyte is then injected and sealed. The cell is then subjected to a series of processes, including settling, formation, aging, and capacity testing, to obtain a soft-pack lithium-ion battery with a rated capacity of 1 Ah.
[0097] Examples 2-5 Examples 2-5 each provide a lithium-ion battery, the only difference between their preparation methods and those in Example 1 being the Dv of the PEG-PLA particles. 50 The differences are shown in Table 1.
[0098] Examples 6-9 Examples 6-9 each provide a lithium-ion battery, the only difference between which is the preparation method and that of Example 1, that is, the molecular weight of PEG-PLA is different, as shown in Table 1.
[0099] Examples 10-13 Examples 10-13 each provide a lithium-ion battery, the only difference between which is the preparation method and that of Example 1, that is, the content of PEG and PLA in PEG-PLA is different, as shown in Table 1.
[0100] Examples 14-17 Examples 14-17 provide a lithium-ion battery, the only difference between which is the preparation method and that of Example 1, that is, the content of PEG-PLA particles in the negative electrode precursor is different (the content of negative electrode active material is adjusted to make the total amount 100%), as shown in Table 1.
[0101] Example 18 This embodiment provides a lithium-ion battery, the only difference between its preparation method and that of Embodiment 1 is that the vacuum degree during heat treatment in step (2) is -20 kPa.
[0102] Example 19 This embodiment provides a lithium-ion battery, the preparation method of which is as follows: (1) Preparation of porous positive electrode sheet LiNi, the positive electrode active material 0.8 Co 0.1 Mn 0.1 O2 (NCM811), conductive agent superconducting carbon black (SP), binder PVDF, and polyethylene glycol-polylactic acid copolymer (PEG-PLA) particles are mixed in a mass ratio of 97:1:1:1, and solvent is added. N 1,3-methylpyrrolidone (NMP) was stirred until homogeneous to obtain a positive electrode slurry (solid content 50%); wherein, the Dv of NCM811 particles was... 50 The Dv of PEG-PLA particles is 5μm. 50 It has a particle size of 5μm, a molecular weight of 6000, a PEG content of 82%, and a PLA content of 18%. The positive electrode slurry was coated on both sides of the positive electrode current collector aluminum foil, air-dried at room temperature, and then transferred to a vacuum drying oven at 115℃ for complete drying. It was then rolled to obtain the positive electrode precursor, with a single-sided areal density of 20 mg / cm³. 2 The compacted density is 3.4 g / cm³. 3 ; The positive electrode precursor was placed in a vacuum heating winding machine for heat treatment. The vacuum degree was controlled at -60 kPa, the heating rate was 5℃ / min, the heating temperature was 200℃, and the heat treatment was carried out for 15 min to obtain a porous positive electrode.
[0103] (2) Preparation of negative electrode sheet The negative electrode active material graphite, the conductive agent superconducting carbon black (SP), the thickener (CMC), and the binder styrene-butadiene rubber (SBR) were mixed in a mass ratio of 96.5:1.5:1:2, and then added to deionized water and stirred evenly to obtain a negative electrode slurry (solid content of 50%). The negative electrode slurry was coated on both sides of the negative electrode current collector copper foil, dried at room temperature, and then transferred to a vacuum drying oven at 115℃ for complete drying. Afterward, it was rolled to obtain a negative electrode sheet with a single-sided areal density of 20 mg / cm³. 2 The compacted density is 1.55 g / cm³. 3 .
[0104] (3) Electrolyte The electrolyte is a solution containing 1 mol / L LiPF6, wherein the solvent is composed of EC, EMC and DEC in a mass ratio of 30:50:20.
[0105] (4) Separator: PE is used as the separator.
[0106] (5) Battery assembly The porous positive electrode, separator, and negative electrode are stacked in sequence to obtain a bare cell. The bare cell is then welded with tabs and placed in an aluminum-plastic film. It is then baked at 80°C to remove water, injected with the electrolyte, and sealed. The cell is then subjected to a series of processes including settling, formation, aging, and capacity testing to obtain a soft-pack lithium-ion battery with a rated capacity of 1 Ah.
[0107] Comparative Example 1 This comparative example provides a lithium-ion battery whose preparation method differs from that of Example 1 only in that the negative electrode precursor does not contain PEG-PLA particles (the content of the negative electrode active material is adjusted to make the total amount 100%).
[0108] Table 1
[0109] Performance testing The performance of the porous electrode and lithium-ion battery prepared in the above embodiments was tested, and the test method is as follows.
[0110] (1) Porosity The porosity of the electrode was determined using the mercury intrusion porosimetry method. The core principle is to utilize the non-wetting and high surface tension properties of mercury (quicksilver) to force it into the pores of the material by applying external pressure. The pore size and distribution are then calculated based on the applied pressure and the volume of mercury intruded. The main testing steps are as follows: A completely dry porous electrode of a certain area is placed in the container of the mercury intrusion porosimeter. The system is evacuated to remove as much air as possible from the container and electrode pores. Under vacuum conditions, mercury is gradually injected into the container, completely surrounding the sample, with the pressure inside the container gradually increasing. As the pressure increases, metallic mercury is gradually forced into the pores of the porous electrode in the following order: macropores, micropores, mesopores, and small mesopores. After the test is completed, the porosity of the porous electrode is calculated based on the mercury intrusion porosimetry results.
[0111] (2) Fast charging performance The porosity of the electrode is closely related to the fast-charging capability of the battery cell, while the lithium plating condition of the negative electrode can reflect the battery's fast-charging capability. The lithium-ion battery provided in the above embodiment was placed in a 25°C constant temperature chamber for 1 hour, then charged at a constant current of 2C to the upper limit voltage, and then charged at a constant voltage until the cutoff current was 0.05C. After standing for 10 minutes, the battery cell was disassembled, and the state of the negative electrode was observed to identify whether lithium plating occurred and the percentage of lithium plating area (the percentage of the negative electrode's lithium plating area to the total area of the negative electrode sheet).
[0112] The results of the above performance tests are shown in Table 2.
[0113] Table 2
[0114] As can be seen from the experimental results in Table 2, compared with Comparative Example 1, the method of this application embodiment can effectively improve the porosity of the electrode, reduce lithium plating on the negative electrode, and improve the fast charging performance of the battery.
[0115] Compared to Example 1, in Example 2, the ratio of the particle size of PEG-PLA particles to the particle size of the negative electrode active material is smaller. This makes it easier for PEG-PLA particles to disperse in the gaps between the negative electrode active material particles, occupying pre-existing gaps. The decomposition of PEG-PLA particles has a smaller effect on improving the porosity of the electrode, thus reducing the improvement in battery fast-charging performance. In Example 5, compared to Example 1, the ratio of the particle size of PEG-PLA particles to the particle size of the negative electrode active material is larger. While this can further improve the porosity of the electrode, it also leads to excessively large pores, significantly disrupting the contact between the negative electrode active material particles, thus reducing the improvement in battery fast-charging performance.
[0116] Compared to Example 1, the PEG-PLA in Example 6 has a smaller molecular weight and a lower thermal decomposition temperature, making it prone to decomposition during coating and drying. The resulting pores are damaged by rolling, thus reducing the porosity of the porous negative electrode sheet after heat treatment, increasing the lithium plating area, and decreasing the improvement in battery fast-charging performance. Compared to Example 1, the PEG-PLA in Example 9 has a larger molecular weight, making PEG-PLA particles prone to agglomeration. Although the increased particle size after agglomeration can improve porosity to some extent, it also leads to poorer particle dispersion uniformity. This results in poorer pore size and distribution uniformity in the obtained porous negative electrode sheet, thus increasing the lithium plating area and decreasing the improvement in battery fast-charging performance.
[0117] Compared to Example 1, the PEG-PLA particles in Example 10 have a lower PEG content and a higher PLA content, resulting in a higher thermal decomposition temperature of PEG-PLA. With the heat treatment temperature and time remaining constant, the residual amount of PEG-PLA particles increases, thus reducing the porosity of the porous negative electrode sheet, increasing the lithium plating area, and decreasing the improvement in battery fast-charging performance. Compared to Example 1, the PEG-PLA particles in Example 13 have a higher PEG content and a lower PLA content, resulting in a lower thermal decomposition temperature of PEG-PLA. This makes it prone to decomposition during coating and drying, and the resulting pores are damaged by rolling. Furthermore, the hygroscopic nature of PEG easily leads to poor uniformity of the negative electrode slurry. Therefore, after heat treatment, the porosity of the porous negative electrode sheet decreases, the pore distribution uniformity deteriorates, the lithium plating area increases, and the improvement in battery fast-charging performance decreases.
[0118] Compared to Example 1, Example 14 used less PEG-PLA particles, resulting in reduced porosity of the porous negative electrode sheet, increased lithium plating area, and decreased improvement in battery fast-charging performance. Compared to Example 1, Example 17 used more PEG-PLA particles. While this increased the porosity of the porous negative electrode sheet, it also significantly disrupted the contact between the active material particles, hindering ion transport and thus reducing the improvement in battery fast-charging performance.
[0119] Compared with Example 1, Example 18 has a lower vacuum (i.e., higher absolute pressure) and more residual oxygen in the environment, which makes PEG-PLA particles more likely to decompose into non-volatile substances. Moreover, under the condition that the heat treatment temperature and time remain unchanged, the degree of decomposition of PEG-PLA particles will also decrease. Therefore, the porosity of the porous negative electrode sheet is reduced, and the improvement effect of battery fast charging performance is reduced.
[0120] Example 19 successfully prepared a porous positive electrode by adding PEG-PLA particles to the positive electrode material. The positive electrode has little effect on the lithium plating condition of the negative electrode. However, the test showed that compared with Comparative Example 1, the liquid retention coefficient and cycle performance of the positive electrode in Example 19 were significantly improved, and the DCR was significantly reduced. Therefore, it is shown that the porous positive electrode prepared by the method of this application can also effectively improve the fast charging performance of the battery.
[0121] The above description is merely a specific embodiment of this application, enabling those skilled in the art to understand or implement this application. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of this application. Therefore, this application is not to be limited to the embodiments described herein, but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing a porous electrode sheet, characterized in that, The preparation method includes the following steps: Electrode active material, conductive agent, binder, polyethylene glycol-polylactic acid copolymer particles and solvent are mixed to prepare electrode slurry, wherein the polyethylene glycol-polylactic acid copolymer particles are insoluble in the solvent; The electrode paste is coated on at least one side of the current collector, and after drying and rolling, the electrode paste on the surface of the current collector forms an electrode active layer precursor, thus obtaining an electrode precursor. The electrode precursor is heat-treated to decompose the polyethylene glycol-polylactic acid copolymer and generate pores, thus obtaining a porous electrode.
2. The preparation method according to claim 1, characterized in that, The Dv of the polyethylene glycol-polylactic acid copolymer particles 50 With the Dv of the electrode active material 50 The ratio is 0.1-2:
1.
3. The preparation method according to claim 1 or 2, characterized in that, The thermal decomposition temperature of the polyethylene glycol-polylactic acid copolymer is 150-200℃.
4. The preparation method according to any one of claims 1-3, characterized in that, The weight-average molecular weight of the polyethylene glycol-polylactic acid copolymer is 3000-10000 Da; And / or, in the polyethylene glycol-polylactic acid copolymer, the content of polyethylene glycol is 80-85 wt% and the content of polylactic acid is 15-20 wt%.
5. The preparation method according to any one of claims 1-4, characterized in that, The mass content of the polyethylene glycol-polylactic acid copolymer particles in the electrode active layer precursor is 0.1-1%.
6. The preparation method according to any one of claims 1-5, characterized in that, The electrode active layer precursor comprises, by weight percentage: 1-10% conductive agent, 2-10% binder, 0.1-1% polyethylene glycol-polylactic acid copolymer particles, and the balance being electrode active material.
7. The preparation method according to claim 6, characterized in that, The electrode active layer precursor also includes 0.5-1 wt% thickener.
8. The preparation method according to any one of claims 1-7, characterized in that, The heat treatment temperature is T~T+25℃, where T is the thermal decomposition temperature of the polyethylene glycol-polylactic acid copolymer. The heat treatment time is 10-120 min.
9. The preparation method according to any one of claims 1-8, characterized in that, The heat treatment is carried out under vacuum conditions of -40 to -80 kPa.
10. The preparation method according to any one of claims 1-9, characterized in that, The solid content of the electrode slurry is 30-60%.
11. The preparation method according to any one of claims 1-10, characterized in that, The porous electrode sheet is a negative electrode sheet, and the compaction density of the electrode active layer precursor in the electrode sheet precursor is 1.4-1.8 g / cm³. 3 ; Alternatively, the porous electrode sheet is a positive electrode sheet, and the compaction density of the electrode active layer precursor in the electrode sheet precursor is 2.1-3.8 g / cm³. 3 .
12. A porous electrode sheet, characterized in that, It is prepared by the preparation method according to any one of claims 1-11.
13. A secondary battery, characterized in that, The secondary battery includes the porous electrode sheet as described in claim 12.
Citation Information
Patent Citations
Adaptive Truck Bed Storage System
KR1020200123456A
Quantum waveguide infrared photodetector
US20210028214A1